The influences of patient's trust in medical service and attitude towards health policy on patient's overall satisfaction with medical service and sub satisfaction in China - Tang Liyang (BMC, 2011)
Abstract Background It is widely accepted that patient generates overall satisfaction with medical service and sub satisfaction on the basis of response to patient's trust in medical service and response to patient's attitude towards health policy in China. This study aimed to investigate the correlations between patient's trust in medical service/patient's attitude towards health policy and patient's overall satisfaction with medical service/sub satisfaction in current medical experience and find inspiration for future reform of China's health delivery system on improving patient's overall satisfaction with medical service and sub satisfaction in considering patient's trust in medical service and patient's attitude towards health policy. Methods This study collaborated with the National Bureau of Statistics to collect a sample of 3,424 residents from 17 provinces and municipalities in a 2008 China household survey on patient's trust in medical service, patient's attitude towards health policy, patient's overall satisfaction and sub satisfaction in current medical experience. Results Patient's overall satisfaction with medical service and most kinds of sub satisfaction in current medical experience were significantly influenced by both patient's trust in medical service and patient's attitude towards health policy; among all kinds of sub satisfaction in current medical experience, patient's trust in medical service/patient's attitude towards health policy had the largest influence on patient's satisfaction with medical costs, the influences of patient's trust in medical service/patient's attitude towards health policy on patient's satisfaction with doctor-patient interaction and satisfaction with treatment process were at medium-level, patient's trust in medical service/patient's attitude towards health policy had the smallest influence on patient's satisfaction with medical facilities and hospital environment, while patient's satisfaction with waiting time in hospital was not influenced by patient's trust in medical service/patient's attitude towards health policy. Conclusion In order to improve patient's overall satisfaction with medical service and sub satisfaction in considering patient's trust in medical service and patient's attitude towards health policy, both improving patient's interpersonal trust in medical service from individual's own medical experience/public trust in medical service and improving patient's attitude towards health policy were indirect but effective ways.